Længsel efter positiv frihed - Schramm, Moritz (Passage - Tidsskrift for litteratur og kritik, 2011)
Moritz Schramm: “Longing for Positive Freedom. Social Utopias in Kafka’s Short Prose Text “Der Ausflug ins Gebirge”” Since Hans Thies Lehmann’s essay from 1984 on Franz Kafka’s early short prose text, “Der Ausflug ins Gebirge” (1910), it has been read as an “allegory of language”. From this point of view the text mirrors the alleged tendency in Kafka’s works to reduce referentiality in articulating instead the writing-process in literature itself. Focusing on the social interactions in “Der Ausflug ins Gebirge” this essay proposes a different reading. According to this reading, the text opens for a new understanding of the utopian thinking in Kafka’s works, where the notion of positive freedom and the struggle for recognition are particularly important.